High Reliability and Performance PWM Inverter for Standalone Microgrids - Botterón, Fernando (2013)
In this paper a high reliability and performance single-phase PWM inverter for standalone microgrids is presented. To obtain the before mentioned characteristics this work propose, two different controller structures and a straightforward design methodology for these controllers, based on the internal model principle. In order to validate the proposed design methodology, digital controllers and to demonstrate the steady state and transient performance, experimental results are presented from a 5kVA PWM modulated single-phase inverter, fully controlled by a DSP TMS320F2407.